Gamification Of Islamic Education: Exploring The Role Of Wordwalls In Increasing Student Participation In Learning The Qur'an And Hadith - Anwar, Muhammad Adib; Inayati, Nurul Latifatul (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
The use of Wordwall media in learning Qur’an Hadith has proven to be quite effective. Students appear more engaged and active when completing the interactive questions and games provided through the Wordwall platform. This media offers a user-friendly and dynamic way for students to respond to questions, making the learning experience more enjoyable. The use of engaging and varied instructional media is essential for teachers aiming to foster active student participation, ensuring that learning is not solely teacher-centered but also involves students meaningfully. Wordwall, as a web-based learning tool, serves as an alternative solution to address challenges related to student engagement and focus during the learning process. The purpose of this study is to examine the effectiveness of Wordwall media in increasing student participation. Utilizing a qualitative research method, the data in this study is presented in the form of descriptive narratives, aligning with the principles of a qualitative approach. Viewed from the perspective of the research problem, this study falls into the category of descriptive research. Descriptive research involves collecting data sources and processing them into information that helps address the research questions particularly those related to current conditions. It aims to objectively describe the state of a subject or phenomenon based on observed realities.